Strategi Public Relations dalam Mempertahankan Eksistensi Pasar Malam - Rusydi, Fahreza Syaifullah; Wibawa, Darajat; Tresnawaty, Betty (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2021)
This study aims to describe the process of the public relations strategy by the Kelana Jaya Putra Night Market in order to maintain existence. The concept used four step public relations in the form of; problem identification, program planning, taking action and communication and evaluation. The paradigm used is the constructivism paradigm with a qualitative descriptive method. The data collected in this study through interviews assisted by observation and literature study. The results of the study show that the public relations strategy used at Kelana Jaya Putra Night Market begins with stage (1) identification of problems internally and externally including; coordination, consultation, discussion, monitoring, observation and survey. Stage (2) program planning includes; preparation of plans and budgets, program planning in maintaining existence. Stage (3) taking action and communication, including promotion using online media, holding discussions with various parties including UMKM. Stage (4) evaluation includes; observation, monitoring and coordination.